Japanese imperialism, 1894-1945 - Beasley, W. G. (William G.), 1919-2006 (Clarendon Press ; Oxford University Press, 1987)
A study of the origins and nature of Japanese imperialism from the Sino-Japanese War until its collapse following World War II. The author describes how Japan's aims were influenced by growing industrialization and its experience of Western imperialism.